(untitled) (The International Journal of Educational Sciences and Arts, 2026)
This study aimed to investigate the use of the Eisenkraft constructivist model in secondary education. It focused on the issue of insufficient development in students’ inquiry thinking skills and their various abilities, as well as their application in accessing knowledge and experiences. To achieve its objectives, the researcher adopted a quasi-experimental approach using a single-group design. The study sample consisted of 29 second-year secondary school students in Al-Namas Governorate. The researcher prepared a teacher’s guide that included the steps for implementing the Eisenkraft model in a selected unit from the second-year secondary physics curriculum. The study also involved the development of an achievement test to measure students’ skills and acquired knowledge. The results demonstrated the effectiveness of applying the Eisenkraft model in teaching the selected unit. Based on these findings, the researcher recommended the adoption of teaching methods and strategies that enhance inquiry-based thinking skills, as well as promoting positive attitudes toward subjects that contribute to meeting the needs of society.